Resolving the Problems of Early Marriage in the Religious Courts: An Analysis of the Assessment of the Institute for the Protection of Women and Children - Najib, Achmad; Sakirman; Fatarib, Husnul (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Purpose – The main purpose of this research article is to analyze the significance of the assessment conducted by the Gunung Sugih Women and Children Protection Agency (LPPA) on marriage dispensation applications at the Gunung Sugih Class I B Religious Court. Methods – The Class 1B Gunung Sugih Religious Court serves as the location of a specific type of field research. This research used a juridical-empirical approach to gather information. Primary and secondary sources were used as data sources. Judges in charge of reviewing marriage dispensation cases and LPPAs who provided recommendations for judgment were the primary data sources. In contrast, all data not obtained from primary sources were considered secondary data sources in this study. Findings – The Women and Child Protection Agency (LPPA) of Gunung Sugih plays an important role in the marriage dispensation application process at the Religious Court Class I B Gunung Sugih. Their assessment is crucial as they conduct a thorough evaluation of the prospective bride and groom, taking into account their understanding of religious issues, psychological readiness, mental well-being, commitment to their future children, the stability of their children, and the family's financial situation. The ultimate goal is to ensure that decisions regarding marriage dispensation are taken following the principle of maslahah, which prioritizes the long-term welfare of both individuals and society.